2016
DOI: 10.1177/2058460116652651
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of amniotic fluid index (AFI) in third trimester with fetal weight and gender in a southeast Nigerian population

Abstract: BackgroundAmniotic fluid (AF) is one of the major determinants of fetal biophysical profile and can predict pregnancy outcome. Abnormal value of amniotic fluid index (AFI) may indicate fetal and maternal disorders.PurposeTo establish reference standards for AFI for this population after 28 weeks of pregnancy and evaluate the relationship between AFI, the estimated fetal weight (EFWT), and fetal gender.Material and MethodsA prospective cross-sectional estimation of AFI and FWT was done in 385 apparently healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These results concurred with the results of the study done by Brace et al (21). The reason why literature studies present different results is that AFI values may change depending on many factors such as ethnicity, geographical region, socio-economical factors (22). Meanwhile, the current study suggested no significant correlation between age and parity and AFI.…”
Section: Discussionsupporting
confidence: 91%
“…These results concurred with the results of the study done by Brace et al (21). The reason why literature studies present different results is that AFI values may change depending on many factors such as ethnicity, geographical region, socio-economical factors (22). Meanwhile, the current study suggested no significant correlation between age and parity and AFI.…”
Section: Discussionsupporting
confidence: 91%
“…Amniotic uid index [AFI] and single deepest pocket [SDP] are the most-used semiquantitative techniques. AFI is calculated by summing the depth in centimeters of 4 different pockets of uid not containing cord or fetal extremities in 4 abdominal quadrants using the umbilicus as a reference point and with the transducer perpendicular to the oor [4,21,22]. SDP refers to the vertical dimension of the largest pocket of amniotic uid [with a horizontal measure of at least 1 cm not containing umbilical cord or fetal extremities and measured at a right angle to the uterine contour and perpendicular to the oor.…”
Section: Methods Of Determining Amniotic Uid Volumementioning
confidence: 99%
“…AFI values most especially in third trimester are proportionate to the fetal urine production, nutrients and oxygen transfer [23]. Hence, monitoring the AFI has become a standard of antenatal care [32,33]. In this study, the gestation specific percentage values of amniotic fluid index have been formulated for the uncomplicated pregnant Abuja women.…”
Section: Discussionmentioning
confidence: 99%